33. Intranasal M2SR (M2-deficient Single Replication) Live H3N2 Influenza Investigational Vaccine Induces Serum HAI & Broad Immune Responses in High Proportion of Adults. (31st December 2020) - Eiden, Joseph; Ellis, Ruth; Fierro, Carlos; Schwartz, Howard; Adams, Mark; Ellis, Kimberly; Aitchison, Roger; Herber, Renee; Bilsel, Pamuk
Abstract: Background: A single intranasal (IN) dose of 10 8 TCID50 M2SR protected a responder subset of adults against infection and disease in a prior human influenza challenge study (EudraCT number: 2017-004971-30). Higher dose levels of M2SR were assessed in this phase 1b study to enhance immune responses and further increase protection levels in adults. Methods: A double-blind, randomized, placebo-controlled dose escalation study (NCT03999554) was conducted at 4 US study sites with two different H3N2 M2SR vaccines that contained HA & NA from either A/Brisbane/10/2007 or A/Singapore/INFIMH-16–0019/2016. Serosusceptible 18–49 year old subjects (n = 206) received 2 IN doses of either saline or 1 of 3 different dose levels of vaccine (10 8 – 10 9 TCID50 ), administered 28 days apart. Results: Study vaccination was well-tolerated at all dose levels. A single 10 9 dose of A/Singapore/2016 M2SR generated significantly increased serum HAI responses compared to the 108 dose of A/Brisbane/10/2007 M2SR that had provided protection against infection & illness in an earlier human influenza challenge study (Fig. 1 ). HAI titers ≥40 were achieved in 0%, 23% & 58% of subjects after the first dose of placebo, 10 8 or 10 9 M2SR, respectively (p< 0.003). Increases also were stimulated in serum microneutralization titers (MNT) to drifted strains of H3N2 (Fig 2) & in serum NAI (Fig 3 ) and mucosal sIgA (Fig 4 ) titers. Further increases in serum and mucosal immune response were noted after a 2 nd IN vaccination. Proportion of subjects with seroprotective HAI titers after vaccination Proportion of subjects with increased microneutralization titers against drifted H3N2 viruses after vaccination Geometric mean fold rise in serum neuraminidase inhibition antibody titers after vaccination Conclusion: An earlier clinical trial with a 10 8 dose of M2SR provided protection against infection and illness upon challenge with a highly drifted strain of H3N2. Protection correlated with vaccine induced serum MNT responses. In the current study, a single, 10 9 dose of M2SR significantly increased serum MNT, HAI & NAI titers as well as mucosal immune responses among greater proportions of study subjects. Since HAI, alone, is a well-accepted surrogate marker for vaccine protection against influenza, these broader enhancements indicate the potential for M2SR to protect against both matched and drifted strains of influenza in a high proportion of adults and strongly support clinical assessment in younger and older age groups as well as development of multivalent M2SR. Geometric mean fold rise in nasal mucosal secretory IgA antibody titers after vaccination Disclosures: Joseph Eiden, MD, PhD, FluGen (Consultant) Ruth Ellis, MD, FluGen (Consultant) Roger Aitchison, ScM, FluGen (Consultant) Renee Herber, BS, FluGen (Employee) Pamuk Bilsel, PhD, FluGen (Employee)